Development of Virtual Tours for Baba Nyonya Museum Using Mixed Reality Portal Technology - NG, YEE VON; Senan, Norhalina (Applied Information Technology And Computer Science, 2024)
Baba Nyonya, also called Peranakan Chinese or STRAITS-born Chinese, is one of the iconic cultures in Malaysia. Today, to preserve their culture, their descendants have established the Baba Nyonya Museum. However, the present resources online and museums established related to Baba Nyonya are limited. Thus, an application that can let the public visit the Baba Nyonya Museum in an alternative way is proposed. XR Nyonya Walk is a mobile-based application developed on the Android platform is developed with Multimedia Mobile Content Development (MMCD) methodology using Unity Software with the implementation of XR origin. The application is initiated to boost tourism in Malaysia by digging into the unique cultural heritage of Malaysia. It was highly hoped that the XR Nyonya Walk would be used by the public as an alternative way to learn about the culture of Baba Nyonya and to visit to Baba Nyonya Museum.